Work Engagement Relationship With Nurse Intention Turnover At Porsea Hospital - Dosmaida Nababan; Tumpal Manurung; Elisabeth Vebiola Sianipar (International Journal of Health Engineering and Technology, 2024)
Work engagement can be one of many predictors of turnover intention in nurses. Turnover intention can be minimized, so that it can reduce the nurse turnover rate in a company. The purpose of this study was to determine the relationship between work engagement and nurse turnover intention. This study used a cross-sectional design with chi-square test. This research was conducted in September – December 2023, with 140 nurses as the sample. The sampling technique used in this study was stratified random sampling. Based on the results of the analysis between turnover intention and work engagement has got p-value = 0.001 (p <0.05) was obtained and the results of the analysis between the characteristics of nurses and turnover intention showed has got p-value = 0.244 -0.831 (p <0.05). The conclusion of this study is that there is a significant relationship between turnover intention and work engagement at Porsea Hospital and there is no relationship between nurse characteristics and the incidence of nurse turnover intention at Porsea Hospital. It is expected that the hospital management can maintain a good level of work engagement in hope it can reduce nurse turnover rates. Hospitals can facilitate various things that support work engagement, such as a good environment, adequate compensation, and feedback   the work of nurses.